Career desires and expectations of event management students. (September 2017) - Stone, Matthew J.; Padron, Thomas C.; Wray, Michael L.; La Lopa, Joseph "Mick"; Olson, Eric D.
Abstract: This study measured the factors that undergraduate event management (EM) students perceive to be important in choosing a career, determine the expectations of an event career by EM students, and compare importance and expectation factors. Drawing on Social Cognitive Career Theory, this study surveyed 525 students from five U.S. universities. The most important attributes for choosing a career in EM were: an enjoyable job, pleasant working environment, and an exciting job. For expectations of a career in EM, students felt an EM career most highly offered: interaction with others, an enjoyable job, responsibility, excitement, and transferable skills. In general, students reported desired importance factors which exceeded expectation levels. However, findings indicate students are aware of weaknesses of EM careers. Implications for students, educators, universities, and industry are discussed.